1998
DOI: 10.1093/protein/11.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of an antibody against human protein C and calcium- dependence involving framework residues

Abstract: A murine monoclonal antibody to the zymogen form of human protein C that blocks protein C activation by thrombin-thrombomodulin both in vitro and in vivo has been humanized using the consensus and resurfacing methods. While the binding of the parent murine antibody to protein C is calcium-dependent (1.5-2-fold decrease in binding without calcium), the humanized antibody exhibited a significant increase in its calcium-dependence (5-fold decrease in binding without calcium). Two exposed human framework residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…Humanization of anti-human protein C mAb resulted in the humanized form exhibiting a signi®cant increase in calcium-dependence for binding compared with its murine counterpart [35]. Evaluation of antibody variants indicated human FR residues, AspL1 and GlnL3, in the VL region were involved in the increased calcium-dependence [35]. We also found an increase in ADCC of the humanized anti-GM2 mAb against GM2-expressing cancer cells compared with the chimeric mAb [34].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Humanization of anti-human protein C mAb resulted in the humanized form exhibiting a signi®cant increase in calcium-dependence for binding compared with its murine counterpart [35]. Evaluation of antibody variants indicated human FR residues, AspL1 and GlnL3, in the VL region were involved in the increased calcium-dependence [35]. We also found an increase in ADCC of the humanized anti-GM2 mAb against GM2-expressing cancer cells compared with the chimeric mAb [34].…”
Section: Discussionmentioning
confidence: 92%
“…The humanized anti-p185 HER2 mAb bound to the antigen 3 times more tightly than its murine counterpart and, in contrast, had a potency equivalent to the murine mAb in blocking antigen-positive cell proliferation [4]. Humanization of anti-human protein C mAb resulted in the humanized form exhibiting a signi®cant increase in calcium-dependence for binding compared with its murine counterpart [35]. Evaluation of antibody variants indicated human FR residues, AspL1 and GlnL3, in the VL region were involved in the increased calcium-dependence [35].…”
Section: Discussionmentioning
confidence: 99%
“…3). This difference likely originates from the very nature of the antibody-antigen binding interaction, which was also found to be affected by the [Ca 2+ ] [39,40]. O'Connor et al [39] observed a 1.5-to 2-fold decrease in the binding of the parent murine antibody to protein C in conditions without Ca 2+ ; the human antibody exhibited a 5-fold stronger dependence on Ca 2+ .…”
Section: The Peak Calcium Response Evoked By Als Igg Is Achieved By Rmentioning
confidence: 99%
“…This difference likely originates from the very nature of the antibody-antigen binding interaction, which was also found to be affected by the [Ca 2+ ] [39,40]. O'Connor et al [39] observed a 1.5-to 2-fold decrease in the binding of the parent murine antibody to protein C in conditions without Ca 2+ ; the human antibody exhibited a 5-fold stronger dependence on Ca 2+ . Thus, the prolonged delay to onset and time to peak response in Ca 2+ -free ECS may be explained by the decreased binding efficacy of ALS IgG to the antigen, which may result in less efficient signaling downstream of the IgG binding and the delayed onset of the response.…”
Section: The Peak Calcium Response Evoked By Als Igg Is Achieved By Rmentioning
confidence: 99%
“…We examined the sequence of the murine antibody HPC4 which was humanized by O'Connor et al 22 These authors used consensus sequences as human acceptors, selecting a consensus human subgroup VκI light chain and VH-III family heavy chain.…”
Section: Z-score Analysismentioning
confidence: 99%